2021
DOI: 10.1021/acsami.1c11862
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Humidity-Responsive Actuation of Polymer Films Enabled by Combining Shape Memory Property and Surface-Tunable Hygroscopicity

Abstract: Most humidity-responsive polymeric actuators can only exhibit shape transformations between a planar shape in the dry state and a bended three-dimensional (3D) shape when exposed to moisture, and it is challenging to design and prepare hygroscopic actuators with programmable actuating behaviors displayed from sophisticated 3D structures. Herein, we demonstrate that the integration of shape memory property and surface treatment enabled hygromorphic responsivity endows a single-component polymer film with progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Soft polymeric actuators have garnered much interest over the past decade due to their potential applications, including microfluidic devices, artificial muscles, and soft robotics. Various stimuli-responsive polymeric systems were developed, which change shape when exposed to light, electric or magnetic fields, , humidity, pH, , or temperature. , More recently, examples of combined actuators and programmable shape-memory materials have been reported, enabling (re)­programming and reuse of these materials. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Soft polymeric actuators have garnered much interest over the past decade due to their potential applications, including microfluidic devices, artificial muscles, and soft robotics. Various stimuli-responsive polymeric systems were developed, which change shape when exposed to light, electric or magnetic fields, , humidity, pH, , or temperature. , More recently, examples of combined actuators and programmable shape-memory materials have been reported, enabling (re)­programming and reuse of these materials. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive polymer hydrogels that are able to respond to the changes in temperature [ 1 ], pH [ 2 ], humidity [ 3 ], light [ 4 ], specific ions or molecules [ 5 ], electrical fields [ 6 ], solvent [ 7 ] and ionic strength [ 8 ] have been extensively studied due to potential applications in the areas of drug delivery [ 9 ], microlenses [ 10 ], sensors [ 1 ] and artificial organs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the hydrogel materials can respond to humidity changes, it has a slower response speed and less mechanical deformation, 2 and further improvements are needed. Additionally, other polymers containing hydrophilic groups can also respond to humidity changes, such as polyvinyl alcohol (PVA), 51,103 polyethylene oxide (PEO), 32,52,104 chitosan (CS), 105 polyol-borate, 106 polyethylene-co-acrylic acids (EAAs), 107 biaxially oriented polypropylene (BOPP), 108 and some liquid crystal polymers, [109][110][111] which are widely used in various actuation studies. For example, Wang et al demonstrated the continuous response of the actuator to humidity gradients by using PVA films as actuators.…”
Section: Synthetic Material-based Actuatorsmentioning
confidence: 99%